The duty of the agriculturist, and is he living up to it - Abell, Edward Jones (My University, 1895)
Introduction: That agriculture is the most important of all industries, is universally recognized. This wide spread opinion is founded upon the most unshakable of reasons. Man’s subsistence being derived from the soil, its cultivation becomes imperative. Modern agriculture makes possible the existence of the human race in stupendous numbers. North America formerly supported only a few hundred thousand Indians; now it furnishes a home for nearly one hundred million people with wants much more varied than were those of their predecessors. Yet the land is no more fertile—the change is owing wholely to different habits of industry. And still the development of the resources of this country has just begun. Especially is this true of agriculture. It is extensive now, but to support the rapidly increasing population, it will have to be made still more extensive, and not only that, but more intensive.
Citation: Abell, Edward Jones. The duty of the agriculturist, and is he living up to it. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Agriculture; United States; Theses; Manuscripts (documents)